Recent Developments in Cell Permeable Deubiquitinating Enzyme Activity-Based Probes - Conole, Daniel; Mondal, Milon; Majmudar, Jaimeen D.; Tate, Edward W. (Frontiers in Chemistry, 2019)
Deubiquitinating enzymes (DUBs) function to remove or cleave ubiquitin from post-translationally modified protein substrates. There are about 100 known DUBs in the proteome, and their dysregulation has been implicated a number of disease states, but the specific function of many subclass members remains poorly understood. Activity-based probes (ABPs) react covalently with an active site residue to report on specific enzyme activity, and thus represent a powerful method to evaluate cellular and physiological enzyme function and dynamics. Ubiquitin-based ABPs, such as HA-Ub-VME, an epitope-tagged ubiquitin carrying a C terminal reactive warhead, are the leading tool for ‘DUBome’ activity profiling. However these probes are generally cell membrane impermeable, limiting their use to isolated enzymes or lysates. Development of cell-permeable ABPs would allow engagement of DUB enzymes directly within the context of an intact live cell or organism, refining our understanding of physiological and pathological function, and greatly enhancing opportunities for translational research, including target engagement, imaging and biomarker discovery. This mini-review discusses recent developments in small molecule activity-based probes that target DUBs in live cells, and the unique applications of cell-permeable DUB activity-based probes versus their traditional ubiquitin-based counterparts.